Excitation of Two Types of Storm‐Time Pc5 ULF Waves by Ring Current Ions Based on the Magnetosphere‐Ionosphere Coupled Model. Issue 8 (26th August 2022) - Yamakawa, T.; Seki, K.; Amano, T.; Miyoshi, Y.; Takahashi, N.; Nakamizo, A.; Yamamoto, K.
Abstract: Two types of storm‐time Pc5 waves are excited in the magnetosphere–ionosphere coupled model. We conduct magnetosphere–ionosphere (M–I) coupling between geospace environment modeling system for integrated studies‐ring current (GEMSIS‐RC) and GEMSIS‐POTential solver (GEMSIS‐POT) models in order to investigate the excitation of storm‐time Pc5 waves under more realistic conditions. The coupled model enables us to simulate ion transport from the plasma sheet by the convection electric field. First, we find the excitation of fundamental mode Pc5 waves on the dayside. These waves are generated by the drift resonance and driven by positive energy gradient of ion phase space density (PSD). The wave excitation is similar with the case without M–I coupling. Second, we detect second harmonic mode Pc5 waves with high azimuthal wave number in the dusk and premidnight region. The PSD oscillates associated with the waves, and the drift‐bounce resonance occurs at 50–80 keV ions. We find that these ions drift around the Earth and reach the nightside again at t ∼ 4, 500 s, whose time scale is comparable to the drift period of these ions. At that time, inward gradient of the PSD is created, which contributes to the wave growth. This effect does not happen in the case without dawn‐to‐dusk convection electric field driven by Region 1 field aligned current (FAC). We find that the shielding by Region 2 FAC suppresses the flux of newly injected ions at the nightside, inward gradient of the PSD, and power spectra of second harmonic mode waves. Key Points: Two types of poloidal Pc5 waves are reproduced in a magnetosphere–ionosphere coupled model, where the growth rate is positive Fundamental mode Pc5 waves are excited by the drift resonance in the dayside, where ions have positive energy gradient of the PSD Second harmonic Pc5 waves are excited by the drift‐bounce resonance in the duskside, where ions have inward gradient of the PSD